The unresolved enigma of maternal and childhood mortality in Pakistan - Rahman, Sajjad ur; Tohid, Hiba (Journal of Postgraduate Medical Institute, 2014)
Maternal and child survival are not only the targets of WHO's Millennium Development Goals (MDG's) but also a very important outcome indicator of a country's health services. Ever since their implementation in 1990, individual countries as well as development organizations and health care academics have been monitoring and guiding the progress towards achieving the MDG's. The two most recent progress reports, one on Maternal Mortality (MDG-5) and the other on Childhood Mortality (MDG-4) were published by The Lancet on May 2nd, 2014. Both reports are the hard work of a large group of international experts "The Global Burden of Disease (GBD) Study group". The reports present a global, regional as well as country wise progress in reducing Maternal and Childhood Mortality between 1990 and 2013. The reports give a mix feeling of success as well as failure. While some regions and countries have made exceptional progress; the others have failed to do so. It is heart breaking to see that Pakistan is among the top few countries with no or limited progress. Here we present an account of the situation as well as a summary of health care strategies to counter this failure.